Nocardia thailandica Brain Abscess in an Immunocompromised Patient - Muhammad Effendi; Samad Tirmizi; Dayna McManus; Anita J. Huttner; David R. Peaper; Jeffrey E. Topal (Case Reports in Infectious Diseases)
Objectives. Successful treatment for Nocardia thailandica is not well elucidated in the literature. To the best of our knowledge, N. thailandica has not yet been described in the medical literature to cause central nervous system (CNS) infection from brain abscess. We report the case of an immunocompromised patient who underwent successful treatment to treat his brain abscess caused by N. thailandica. Methods. After failing medical therapy, the patient underwent a craniotomy, and tissue was sent for culture. Upon identification by 16S rDNA sequencing, the organism causing infection was identified to be N. thailandica. Results. Based on susceptibilities, the patient was treated with IV ceftriaxone 2 grams daily for five months. The patient demonstrated clinical and radiological improvement which persisted to 7 months after initiation of therapy. Conclusions. To the best of our knowledge, this is the first documented case of a brain abscess due to N. thailandica which was successfully treated. Due to the location of the infection, ceftriaxone was chosen because of optimal CNS penetration. Ceftriaxone monotherapy demonstrated clinical and radiographic treatment success resulting in the successful treatment of this infection.